KONSTRUKSI HUKUM ISLAM TENTANG PEMBATALAN DAN PENCABUTAN WASIAT - Nurnazli, Nurnazli (Ijtimaiyya: Jurnal Pengembangan Masyarakat Islam, 2016)
Washiyah (will, testament) is the message deliveredby someone before his death with a wealth legacyor other messages outside wealth legacy. Washiyahis one of the ways used by the Muslims to getcloser to Allah at the end of his life, so thatgoodness increases. Washiyah can be done withoutthe presence of the recipient, and even carried outin writing, hence washiyah is part of the contractunilaterally. In the construction law, a washiyah canbe revoked or canceled. Revocation andcancellation, in construction law, are two differentthings. Revocation will typically be done beforethe intestate dies because there are certain reasonsthat urge washiyah revocation. While thecancellation will usually occur when nonfulfillmentof the terms that are subjective orobjective related to the washiyah. On the otherhand, the cancellation will be done with theprocedure that conform with the law. This articlewill further explore this focus.